Silver Oxalate: Mechanical Properties and Extreme Negative Mechanical Phenomena. Issue 6 (18th April 2019) - Colmenero, Francisco
Abstract: The crystal structure and mechanical properties of silver oxalate, Ag2 C2 O4, are determined using first‐principles solid‐state methods. The set of calculated mechanical properties include the bulk modulus and its pressure derivatives, the Young and shear moduli, the Poisson's Ratio and the ductility, hardness, and anisotropy indices. Silver oxalate is a highly anisotropic brittle material possessing a small bulk modulus of ≈9.6 GPa. It displays the negative Poisson's ratio (NPR) phenomenon, the value of the lowest NPR having a very large magnitude, −1.27. Besides, it exhibits the most extreme form of the negative linear compressibility (NLC) phenomenon found to date. Silver oxalate displays anisotropic NLC for external pressures in the range −0.1 to −2.4 GPa directed along the [010] crystallographic direction and isotropic NLC for isotropic pressures in the range −0.51 to 13.4 GPa. The lowest value of the negative compressibility, −831.9 ± 10 TPa −1, is found for an isotropic pressure of −0.16 GPa. The absolute value of the computed lowest NLC is extremely large, about three times larger than the absolute value of the lowest NLC found so far. The NLC pressure range is also very wide, its width being more than two times the largest range found to date. Abstract : Silver oxalate exhibits the most extreme form of the negative linear compressibility (NLC) phenomenon found up to date. The absolute value of the lowest compressibility is extremely large, about three times larger than the largest value found so far. The NLC pressure range is also very wide, its width being more than two times the largest range found up to date.